Voice and memory : Indigenous imagination and expression - G N Devy and others Ed; Davis, Geoffrey V Ed; Chakravarty, K K Ed (New Delhi Orient Blackswam, 2011)
Voice and Memory: Indigenous Imagination and Expression is a companion volume to Indigeneity: Culture and Representation. The essays present a critical enquiry into the cultures and literatures of indigenous communities. They deal with their stories of colonial experience, their marginalization and their struggles to avert the decline of their socio-cultural status and the emergence of their voice in the respective national literature. Rather than seeking succour from a human rights regime, Aboriginal peoples have consistently looked for lessons of environmental balance and social regeneration in their own literature, knowledge systems and cultural traditions. The essays in this volume show how these groups have acknowledged, internalized and adapted to their own idiom, linguistic and cultural nuances and expressions left behind as a relic of colonial presence. Further, in their endeavour to analyze the reasons behind their alienation, they have consistently been self critical, holding the white colonists responsible for their current situation, but recognizing and narrating instances of complicity of Aboriginal elders in the persecution of their women. Running through the volume is the view that the indigenous people are agents rather than objects of change. They have the capacity to classify, codify and present their knowledge and perceive and evaluate changes in the environment. The essays also highlight the rejection by Aboriginal groups of the prevailing view of their cultural heritage as a social problem, at odds with the imperatives of contemporary existence. This book is a celebration of indigenous cultures rooted in their physical and cultural environment rather than an archival repository or a museum gallery. Bringing together scholars from across the world, this volume will be of invaluable interest to students and scholars of sociology, anthropology, tribal studies, colonial studies, literature and linguistics.
Keywords: Social Groups; Popular Culture; Literature and Society